Design of Ship Docking Maintenance Scheduling System at PT Pelni (Persero) - Arie Riespalino; Raditya Galih Whendasmoro; Fauziyah Fauziyah (Journal of Mathematics and Technology (MATECH), 2022)
Pelni (Persero) PT is a provider of sea transportation transportation services which include passenger transportation services and inter-island cargo transportation services. The company does not yet have a supporting system to manage ship maintenance schedules. The company uses applications, namely MS-Word and MS-Excel in managing ship maintenance data so that it is vulnerable to errors made accidentally. Therefore, a ship is needed that can support the best service for customers. So far, the company has not used a well-integrated schedule data management information system, this has caused problems in the ship maintenance process which has an impact on the schedule process that is made which takes a long time for interested parties. From the description of the problems that occur, it is designed and built a Web-Based Ship Maintenance Schedule Management Information System (Docking) at PT. Pelni Tanjung Priok Branch which is expected to solve existing problems. For the method of analysis and design used Unified Modeling Language (UML). Web-Based Ship Maintenance Schedule Management Information System (Docking) At PT. Pelni Cab. Tanjung Priok uses the PHP programming language and MySQL as its database. The method used in designing this information system is the Systems Development Life Cycle (SDLC) method. With the existence of the Ship Maintenance Schedule Management Information System (Docking) this can help companies in the process of managing ship maintenance schedules.